IMPLEMENTASI PROGRAM KANG PISMAN DALAM MEMBANGUN KEPEDULIAN LINGKUNGAN MASYARAKAT SEBAGAI WUJUD TANGGUNGJAWAB WARGA NEGARA (STUDI KASUS DI KELURAHAN SUKAMISKIN-KOTA BANDUNG) - Leli Mulyatika, - (2022)
The program of Mr. Pisman is known as 'Kang Pisman' (Reduce, Separate, and Reuse waste) in the location of urban village Sukamiskin is a government regulation to prevent problem waste, this program was made for the purpose to lower trash volume which has been increased over time in landfill, the implementation in this program also needs people contribution, so that without any helper by people around this program won't work as expected. This research is on purpose to know how far the implementation Kang Pisman's program in building community environmental awareness as a form of responsibility of citizens in the Sukamiskin urban village environment. This research was conducted using a qualitative approach with a descriptive method. The data collection techniques carried out by researchers are interviews, observations, documentation studies, and notes. The data analysis techniques carried out were data reduction, data presentation, conclusion drawing and verification, research data validity, member check, and data triangulation. The result shows that the application Kang Pisma's program that located in urban village Sukamiskin In general, it has been implemented quite well, but in practice, there are still several obstacles that hinder the implementation of the program perfectly related to environmental care and civic responsibility, including the lack of facilities (infrastructure) for organic waste management in the level of the hamlet; there are still found uncoordinated relationship between janitors, garbage collectors, and temporary dump manager and territorial elements; limited human resources in the implementation of Kang Pisman's program (eg limited program assistants from DLHK); the absence of a staffing section at the urban village level that specifically deals with the environment and cleanliness; the lack of awareness of some people in protecting their environment (as seen from the number of people's obedience in separating waste from their homes); and the lack of in-depth socialization of the program to the community and the management not paying attention to strategies in attracting public attention. Keywords: Kang Pisman, Community Environmental Concern, Citizen's Responsibility.